A study of interplay between Compensation, Work Environment, and Job Stres on Productivity of PT. XYZ - Pozak, Nisrina Daffa Talitha; Harianto, Kukuh (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study examination's analysis aims to pinpoint the partial and concurrent impacts of workplace stress, work environment, and remuneration on worker productivity. The study's focus is the workers in PT. XYZ company's logistics division, and the sample size is made up of 31 respondents they was determined by the use of purposive sampling. The quantitative correlation methodology is the method employed in this study. Information was gathered by distributing questionnaires, and the results were examined using multiple linear regression analysis, as well as validity and reliability tests and traditional assumptions like normality, linearity, multicollinearity, and heteroscedasticity. The t-test results indicate that employee productivity is somewhat significantly impacted by pay, work environment, and job stress. The F-test's significance score of 0.001 indicates that these three factors simultaneously had a substantial effect on labor productivity. With an index of correlation (R squared) of 0.595, these three factors account for 59.5% of the variation in labor productivity. Therefore, it is anticipated that this research will aid in the development of labor productivity growth plans by using an appropriate technique to analyze the components under study. These three elements must be equally prioritized by the organization in order to increase worker productivity.